2008
DOI: 10.1002/jbm.b.31291
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties and blood compatibility of commercially available diamond‐like carbon coatings for cardiovascular devices

Abstract: The aim of this study was to determine the relationships between the surface properties and blood compatibility of in-use diamond-like carbon (DLC) coatings for cardiovascular components. Commercially available DLC films were characterized with respect to surface topography and wettability, protein adsorption from human plasma, and platelets adhesion/activation. Fibrinogen (Fng) and human serum albumin (HSA) adsorbed onto the sample surfaces were in particular quantified as two of the main proteins involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…The endothelial cell stent coverage showed to be in continuity with the native vascular endothelium. This outcome in an in vivo model is in line with the observations reported in Ma et al [22] and in Fedel et al [39,40] regarding the albumin:fibrinogen selective adsorbtion that was reported for DLC coatings, especially when rich in sp3 bonds. Moreover Fedel [39] observed that DLC coating showed a competitive and stable albumin passivation against fibrinogen.…”
Section: Analysis Of Explanted Stents 821 Endothelizationsupporting
confidence: 91%
See 1 more Smart Citation
“…The endothelial cell stent coverage showed to be in continuity with the native vascular endothelium. This outcome in an in vivo model is in line with the observations reported in Ma et al [22] and in Fedel et al [39,40] regarding the albumin:fibrinogen selective adsorbtion that was reported for DLC coatings, especially when rich in sp3 bonds. Moreover Fedel [39] observed that DLC coating showed a competitive and stable albumin passivation against fibrinogen.…”
Section: Analysis Of Explanted Stents 821 Endothelizationsupporting
confidence: 91%
“…Our results showed that iCarbofilm™ is rich in sp3 bonds (41%) and its nanostructured surface is morphologically and chemically speaking homogeneous, thanks also to its thinness, which preserves the metal substrate smooth surface. These characteristics, as mentioned in several papers [22,40], lead to a selective adsorption of proteins (albumin instead of fibrinogen) and to a very low platelets activation. From the above characteristics and from the cited results it was expected for this new DLC coating an extremely favourable haemocompatibility and a non-inflammatory behaviour.…”
Section: Discussionmentioning
confidence: 93%
“…The Ag prepared nanoparticles substrate was further coated with an ultrathin ta-C film using a multifilm deposition system (Shimadzu, MR3, in SAE Magnetics (H.K) Ltd.)) with a combination of a FCVA (filtered cathodic vacuum arc) gun (Nanofilm Technology International, Singapore). 23 The deposition rate monitored by an ellipsometer was ϳ0.5 Å per second and the film thickness was varied from 5 to 40 Å. Prior to deposition, all the substrates were cleaned by RF-plasma sputtering using Ar ion plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Material surface properties such as wettability, topography, surface potential and surface chemistry have been proven to affect protein adsorption and cellular behavior on biomaterials [23][24][25][26][27]. Material-dependent monocyte/macrophage adhesion, macrophage fusion into foreign body giant cells (FBGC) and cytokine production have been investigated previously using model biomaterials [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%